2022
DOI: 10.1155/2022/6006127
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Cardiovascular Diseases: Sad Realities and Untold Truths regarding Care of Patients in 2022

Abstract: Obstructive sleep apnea (OSA) is one of the most common and serious sleep-related breathing disorders with a high prevalence among patients with cardiovascular (CV) diseases. Despite its widespread presence, OSA remains severely undiagnosed and untreated. CV mortality and morbidity are significantly increased in the presence of OSA as it is associated with an increased risk of resistant hypertension, heart failure, arrhythmias, and coronary artery disease. Evaluation and treatment of OSA should focus on recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 131 publications
(143 reference statements)
0
7
0
Order By: Relevance
“…Cardiovascular risk in OSA has been widely investigated, and there is an excess risk, reportedly mediated by mechanisms such as neuro-hormonal dysregulation, endothelial dysfunction and inflammation [ 12 ]. The main forms of cardiovascular disease observed in patients with OHS include hypertension, heart failure, arrhythmias and coronary artery disease [ 13 ]. Previous studies have shown an improvement in hypertension under CPAP, but there have also been reports of improvements in electrophysiological parameters and cardiac biomarkers [ 6 , 7 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular risk in OSA has been widely investigated, and there is an excess risk, reportedly mediated by mechanisms such as neuro-hormonal dysregulation, endothelial dysfunction and inflammation [ 12 ]. The main forms of cardiovascular disease observed in patients with OHS include hypertension, heart failure, arrhythmias and coronary artery disease [ 13 ]. Previous studies have shown an improvement in hypertension under CPAP, but there have also been reports of improvements in electrophysiological parameters and cardiac biomarkers [ 6 , 7 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ISAACC study, with 3.35 years of follow-up, and the RICCADSA study, with almost 5 years (57 months) of follow-up, also reached similar conclusions [ 17 , 18 ]. However, PAP therapy does seem to be associated with a reduced risk of heart failure, or an improvement in left ventricular ejection fraction [ 13 ]. Most of the prospective studies investigating cardiovascular events were limited to durations of less than 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive sleep apnea has been linked to various cardiovascular complications, such as hypertension, heart failure, coronary artery disease, arrhythmias, and cardiovascular mortality [ 21 ]. Additionally, OSA poses significant risks, including an elevated risk of overweight and obesity, type 2 diabetes, hyperlipidemia, and physical inactivity [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, OSA is linked to other diseases such as diabetes, hypertension, cardiovascular diseases, congestive heart failure, and stroke [ 25 , 26 ]; therefore, OSA can be seen as a risk factor for other diseases. As such, the evaluation and treatment of OSA should focus on the recognition of patients at risk of OSA [ 27 ]. Obesity is the highest risk factor for OSA and it is estimated that 58% of moderate-to-severe OSA development can be attributed to obesity [ 28 ].…”
Section: Introductionmentioning
confidence: 99%